BRINGING GLOBAL ISSUES IN ENGLISH CLASSROOM: Nurturing for a Better World - Muhaimin Muhaimin (ELT-Lectura, 2014)
Global education is a new approach to language teaching that attempts to promote the knowledge,attitudes and skills relevant to living responsibly in a multicultural, interdependent world education. It aims to enable students to effectively acquire a foreign language while empowering them with the knowledge, skills, and commitment required by world citizens to solve global problems. This studies tries to share a perspectives from practitioners that involves to share global education pedagogical approach in the level of universities in Indonesia in order to better prepare students for citizenship in a global age.